STUDY ON THE OPTIMALIZATION OF AGRICULTURE AREA FOR SUSTAINABLE ASIATIC PENNYWORT FARMS BY AL WAHIDAH INTERNATIONAL SDN. BHD. AT THE CITY OF PENANG, MALAYSIA - Siti Fatimah (Teknosains, 2020)
Development of a region intents to harmonize various activities, especially the use of space and resources to sustain community activities in accordance with regional development goals and objectives. Asiatic Pennywort (Centella asiatica) is an herbaceous that is commonly found in temperate and tropical swampy areas and has been utilized as a medicinal herb for centuries. Al Wahidah International, SDN. BHD., a Malaysian halal herbal product company, has been successfully developing a specific agricultural area of Asiatic Pennywort located in Penang, West Malaysia by establishing a system of collaboration between companies and farmers. The farm is located in Kayang Ramban (1 Ha, managed by 2 persons) and Ko Kelang (2.5 Ha, managed by 6 persons). The farm can produce up to 4 tonnes Asiatic Pennywort for one harvest or with a total 3.5 hectares farm can produce 16 tonnes. At the good-rainfall season, the farm can optimally harvest 4 times, while at the less-rainfall season can be 3 times every year. The yield of overall farm for 3 times a year harvesting could reach 48 tonnes.